The Interconnection between Solar and Lunar Systems and Islamic Devotions: A Research Study of Quranic Wisdoms - Dr. Zaheer Ahmad (Journal of Religion and Society, 2025)
This research article provides an in-depth analysis of the dual calendar system in Islam, focusing on the lunar (Hijri) and solar calendars and their implications for religious practices. While daily prayers are determined by solar phenomena, major religious observances such as Ramadan, Hajj, and Eid follow the lunar calendar. The article examines primary sources including the Qur'an, Hadith, classical exegeses, jurisprudential opinions, and modern Islamic astronomical scholarship. It highlights the philosophical, theological, and practical wisdom behind employing both calendars and illustrates how empirical observation and scientific calculation are harmonized within Islamic tradition. The study emphasizes the dual system's role in ensuring global coherence, seasonal flexibility, and alignment with celestial phenomena. Keywords: Lunar Calendar, Solar Calendar, Islamic Worship, Fiqh, Astronomy, Qur'anic Time, Hajj, Ramadan